The role of the state in managing and forestalling systemic financial crises: Some issues and perspectives - Charles Adams (Asian Development Bank Institute (ADBI), 2010)
This paper reviews recent state interventions in financial crises and draws lessons for crisis management. A number of areas are identified where crisis management could be strengthened, including with regard to the tools and instruments used to involve the private sector in crisis resolution (with a view to reducing the recent enhanced role of official bailouts and the associated moral hazard), to allow for the orderly resolution of systemically important financial firms (to make these firms safe to fai), and with regard to achieving better integration with ex ante macroprudential surveillance. The paper proposes the establishment of high level systemic risk councils (SRCs) in each country with responsibility for overseeing systemic risk in both tranquil times and crisis periods and coordinating the activities of key government ministries, agencies, and the central bank.
Keywords: G01; E58; E01; 330; Finanzmarktkrise; Wirtschaftliche Anpassung; Risiko; Kapitalmarktliberalisierung; Wirkungsanalyse; Asien